Mobile Based Coffee Powder Sales Information System in Pagaralam City - Karnadi; Marsela sintya; Syarifah Aini (Universitas Islam Kuantan Singingi, 2025)
The sales information system plays an important role in facilitating the exchange of information and meeting the needs of sellers and buyers. Pagar Alam is a city in South Sumatra Province located at the foot of Mount Dempo, with a strategic geographical position surrounded by mountains and hills. South Sumatra is known as the largest robusta coffee–producing province in Indonesia, supported by extensive plantation areas, high-quality production, and a large number of coffee farmers. However, the Pagar Alam Coffee Powder Shop still applies a conventional sales system that requires buyers to visit the store directly, making the sales process less effective and limiting market reach. In addition to selling ground coffee, the shop actively promotes coffee culture through coffee tasting events and educational activities. To address these challenges, this research aims to design a web-based sales information system that functions as both a sales support tool and a promotional medium. The system is developed as a mobile web optimized for smartphones and tablets, ensuring ease of access and user-friendly interaction. The development process adopts the Waterfall method, which provides a structured and systematic approach through sequential stages to produce an effective and reliable system.